3D printing of nano-cellulosic biomaterials for medical applications. (June 2017) - Sultan, Sahar; Siqueira, Gilberto; Zimmermann, Tanja; Mathew, Aji P.
Abstract: Nanoscaled versions of cellulose viz. cellulose nanofibers (CNF) or cellulose nanocrystals (CNC) isolated from natural resources are being used extensively since the past decade in the biomedical field e.g. for tissue engineering, implants, drug delivery systems, cardiovascular devices, and wound healing due to their remarkable mechanical, chemical and biocompatible properties. In the recent years, 3D printing of nanocellulose in combination with polymers is being studied as a viable route to future regenerative therapy. The printability of nanocellulose hydrogels owing to their shear thinning behavior and the possibility to support living cells allows 3D bioprinting using nanocellulose, a recent development which holds tremendous potential. Graphical abstract: Highlights: 3D printing of nanocellulosic materials is used in biomedical application. Nanocellulose hydrogels have shear thinning behavior and supports living cells. Nanocellulose based biocompatible ink, CELLINK ®, is commercialized by CELLINK AB, Sweden.